Land and Digital Identity: The Potential and Threat of Electronic Certification to Indigenous Peoples - Marasaoly, Salha (PT. Anagata Sembagi Education, 2025)
: Digital transformation in the national land administration system through electronic certification brings hope for increased efficiency, transparency, and legal certainty. However, this modernization also raises serious problems related to structural inequality, especially in relation to customary law communities. Electronic certification based on individual ownership and formal digital identity is not in line with the principles of communal land tenure in customary law. As a result, indigenous peoples who do not have access to digital infrastructure and formal population documents experience digital exclusion which has a direct impact on the marginalization of customary land rights. Customary lands that are not officially documented become vulnerable to claims by other parties, including the state and corporations. This study uses a normative juridical approach by examining the synchronization between the UUPA, the ITE Law, and regulations related to electronic certification, as well as analyzing the acceptance of customary law principles in the digital system. The importance of reformulation of land policies that ensure formal recognition of customary rights through a community-based collective certification mechanism is emphasized. In addition, strengthening inclusive digital identities and the application of Free, Prior and Informed Consent (FPIC) principles are prerequisites to ensure the constitutional protection of indigenous peoples. Without a contextual and social justice-based legal approach, land digitalization risks becoming an instrument of structural exclusion that systemically threatens customary rights.